2021
DOI: 10.1021/acs.cgd.1c00229
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Drug Cocrystallization Simultaneously Improves Pharmaceutical Properties of Genistein and Ligustrazine

Abstract: The oral delivery of genistein (GEN) is hindered by its low bioavailability. The delivery of tetramethylpyrazine (TMP or ligustrazine) is faced with physical instability challenges due to its high sublimation tendency. We tackled respective challenges of the two drugs by forming a cocrystal. The GEN-TMP cocrystal exhibits a significantly reduced sublimation tendency than TMP and a significant enhancement in both the in vitro release rate and bioavailability in rats than GEN. Thus, cocrystallization simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…In addition, the results of TG (Figure 7) indicated that the first weight loss of 24.7% from 160 to 254 • C was reckoned as the loss of the PPZ molecule, whose theoretical weight percentage was 25.3%. To our knowledge, PPZ has a low boiling point of about 146.0 • C. Based on this evidence, it could be predicted that the cocrystal decomposed at 235.47 • C, and PPZ was sublimated with the elevation of temperature, whose phenomenon was similar to the thermodynamic characteristics of solvent compounds and reported in previous studies [25,31,32]. Additionally, it could be found that there was no mass loss to be observed in the test temperature range below the melting point of the DAI-PPZ cocrystal, which indicated that the cocrystal of DAI-PPZ did not contain water or solvents.…”
Section: Thermal Analysissupporting
confidence: 81%
“…In addition, the results of TG (Figure 7) indicated that the first weight loss of 24.7% from 160 to 254 • C was reckoned as the loss of the PPZ molecule, whose theoretical weight percentage was 25.3%. To our knowledge, PPZ has a low boiling point of about 146.0 • C. Based on this evidence, it could be predicted that the cocrystal decomposed at 235.47 • C, and PPZ was sublimated with the elevation of temperature, whose phenomenon was similar to the thermodynamic characteristics of solvent compounds and reported in previous studies [25,31,32]. Additionally, it could be found that there was no mass loss to be observed in the test temperature range below the melting point of the DAI-PPZ cocrystal, which indicated that the cocrystal of DAI-PPZ did not contain water or solvents.…”
Section: Thermal Analysissupporting
confidence: 81%
“…The melting points ( T m s) of PFD, HES, and GEN are 109.6, 231.3, and 306.2 °C, respectively, which are all consistent with the reported data. 18,31,32 For the two cocrystal samples, the endothermic melting signals appear at 116.4 and 137.8 °C, respectively. TGA curves of PFD and the two cocrystals are given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss is very close to the BIP weight percentage in the NITRO–BIP cocrystal (24.7%), but the melting point of pure BIP is very low (about 70 °C), so, at 196.5 °C, its evaporation process should be considered completed. Nevertheless, it is well-known that cocrystallization can significantly affect the thermal stability of the coformer characterized by the higher volatility . Thus, it can be assumed that the first endo event, at 196.5 °C, is associated with the dissociation and release of BIP.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is wellknown that cocrystallization can significantly affect the thermal stability of the coformer characterized by the higher volatility. 58 Thus, it can be assumed that the first endo event, at 196.5 °C, is associated with the dissociation and release of BIP. The second weight loss step at 269.9 °C appears very near that of pure NITRO (272.9 °C), suggesting the sample was predominantly NITRO after the loss of BIP.…”
Section: Methodsmentioning
confidence: 99%